Development and In Vivo Evaluation of Pitavastatin Self-Emulsifying Drug Delivery Systems (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current research was intended at formulation and in vivo evaluation of pitavastatin self-nanoemulsifying drug delivery system (PTN SNEDDS) for enhanced drug dissolution and bioavailability. Solubility studies carried out to construct pseudo ternary phase diagram employing the blends of oil (capmul PG8), surfactant (acrysol K140), and cosurfactant (transcutol P).The PNT SNEDDS prepared and optimized by adopting response surface methodology employing 33 Box-Behnken design. The SNEDDS formulations characterized for % drug content, % entrapment efficiency, in-vitro release studies, particle size, zeta potential, FTIR and SEM studies. The bioavailability studies carried out in wistar rats. The study indicated that PTN12 comprising of 40% capmul PG8, 40% acrysol K140 and 30% transcutol P displayed minimum droplet size (24.8 nm), optimal zeta potential (-10.4 mV) and maximum drug release (98.75%). The SEM data revealed that droplet size is in nanometer range. The pharmacokinetic studies conducted in rats indicated that Cmax of optimized PTN SNEDDS (2.25±0.02ng/ml) was higher than pure PTN suspension (0.75±0.03ng/ml) and optimized SNEDDS exhibited superior oral bioavailability about 4 times of AUC, along with higher plasma concentration than pure drug. The above results indicated that application of SNEDDS formulation technique for PTN increases solubility and dissolution.